The Motivation Climate and Perceived Sport Teachers’ Behavior toward Disciplined – Undisciplined Students - Giannoudis, Γιώργος; Digelidis, Νικόλαος (Inquiries in Physical Education and Sport, 2009)
The purpose of the present study was to examine the function of the perceived expectations of physical education teachers towards students who were characterized either as disciplined or undisciplined. In other words, which were the consequences of their expectations on attitudes, perceptions, intentions towards the physical education lesson and the students’ discipline and reasons for being disciplined. Moreover, it was examined students’ effort, enjoyment, perceived motivational climate and the perceptions of teachers’ differential treatment towards disciplined and undisciplined students. In this study the sample was consistent from 427 ninth grade students (208 boys, 219 girls) from 9 junior high schools of Northern Greece. Results indicated that perceptions of masteryoriented climate were positively related to the reported enjoyment and effort as well as to the students’ task orientation and self – determined reasons for being disciplined. At the same time, mastery-oriented climate was negatively correlated to the negative treatment toward the undisciplined ones. The students who were disciplined, enjoyed their self, tried more, had higher scores in perceived competence scale, had more positive attitudes and intention for discipline than those undisciplined. Moreover, disciplined students were more tasks – oriented and had more self-determined reasons for being disciplined compared with the undisciplined students.